KONTRIBUSI SISTEM AMONG TERHADAP INKLUSI SOSIAL: STUDI KASUS DI SD TAMANSISWA YOGYAKARTA - Miftakhuddin, Miftakhuddin; Khoiron, Muhammad; Wahyuningtyas, Neni (Universitas Negeri Malang, 2023)
THE AMONG SYSTEM'S CONTRIBUTION TO SOCIAL INCLUSION: CASESTUDY AT TAMANSISWA YOGYAKARTA ELEMENTARY SCHOOL Tamansiswa’s among system is a unique teaching model. The teaching model belongs to thefamily of non-directive. In practice, the among system is founded on Tamansiswa's philosophyand belief about the development of students’ knowledge and character, allowing them to be freeto explore their surroundings. So far, the among system has helped to establish both theoreticaland practical frameworks for social inclusion. However, the among system has received littleattention because it is only used in private schools, which the community considers to be lesslegitimate. This study aims to investigate the why and how among system contributes to socialinclusion. In-depth interviews, participatory observation, recording, and anecdotal notes wereused to collect data, which was subsequently validated via triangulation. Data were then analyzedfollowing the procedure introduced by Miles. Based on this analysis, the following importantfindings are highlighted: (a) the among system promotes Gender Equality and Social Inclusion(GESI), (b) the among system prioritizes the fulfillment of children’s rights to receive adequateeducation and development services over academic knowledge, and (c) the among systememploys the humanism-constructivism paradigm (avoiding behaviorism). Practically, thisfoundation is manifested by the teacher by making friends with students based on the norms ofpoliteness, respecting the child’s natural traits, and supervising the child in exercising his or herfreedom (both freedom of thought, speech, and action). The findings of this study havesignificance for the necessity for the adoption of the among system in social studies course inorder to develop social studies learning that is based on genuine experiences in a socialenvironment (contextual). This study's findings also contribute to the development of coreconcepts for implementing the Fun School Movement, culture-based schools, and schools forchildren with special needs. Sistem among merupakan suatu model pengajaran yang khas perguruan Tamansiswa. Modelpengajaran tersebut termasuk dalam rumpun model pengajaran non direktif. Dalam praktiknya,sistem among didasarkan kepada falsafah dan keyakinan Tamansiswa tentang perkembanganpengetahuan dan budi pekerti pelajar, agar mereka merdeka dalam mengenal dunianya. Selamaini, sistem among menyumbang kerangka teoretik maupun praktik terhadap pembangunan inklusisosial. Namun sampai saat ini sistem among kurang diteliti karena hanya terselenggara disekolah swasta yang oleh masyarakat dianggap kurang bonafit. Riset ini berusaha menelaah mengapa dan bagaimana kontribusi sistem among terhadap inklusi sosial secara detail danmendalam. Data diperoleh melalui wawancara mendalam, observasi partisipatif, dokumentasi,dan catatan anekdot, kemudian divalidasi melalui triangulasi. Data yang sahih dianalisismengikuti prosedur yang diperkenalkan Miles. Berdasarkan analisis tersebut, riset ini menyorotitemuan penting berikut: (a) sistem among mempromosikan Gender Equality and Social Inclusion(GESI), (b) alih-alih memprioritaskan pengetahuan akademik, sistem among memprioritaskanpemenuhan hak anak untuk mendapat layanan pendidikan yang layak dan pengembangan budipekerti, dan (c) sistem among menggunakan paradigma humanisme-konstruktivisme(menghindari pola-pola behavioristik). Secara praktis, landasan tersebut dimanifestasikan gurudengan menjalin pertemanan dengan siswa berdasarkan norma kesopanan, menghormati kodratalamiah anak, dan mengawasi anak dalam menggunakan kebebasannya (baik kebebasanberpikir, berucap, maupun bertindak). Temuan riset ini berimplikasi kepada perlunya adopsisistem among dalam pembelajaran IPS agar tercipta pembelajaran IPS berbasis pengalaman riildi lingkungan sosial (kontekstual). Temuan riset ini juga berkontribusi kepada penambahandasar-dasar pelaksanaan Gerakan Sekolah Menyenangkan (GSM), sekolah berbasiskebudayaan, dan sekolah yang mendidik anak berkebutuhan khusus.